Successful treatment with pembrolizumab for microsatellite instability-high thymic carcinoma: A case report - Yuichi Sakamori; Kentaro Hamada; Hiroaki Kawachi; Mako Yamoto; Akari Fukao; Satoshi Terashita; Kizuku Watanabe; Tatsuyoshi Ikeue; Takakazu Sugita (Respiratory Medicine Case Reports, 2025)
Introduction: Thymic carcinoma is a rare, aggressive malignancy, and in cases of metastasis, palliative chemotherapy is the typical treatment. Microsatellite instability (MSI)-high tumors are more likely to respond to immune checkpoint inhibitors, such as pembrolizumab, than to other types of chemotherapy. However, MSI-high thymic carcinoma is extremely rare, with limited reports on the efficacy of pembrolizumab in this context. Case: A 72-year-old woman with metastatic thymic carcinoma (Masaoka stage IVA) and concurrent breast cancer was confirmed to have an MSI-high status through biopsy. Following progression after first-line carboplatin and paclitaxel, pembrolizumab (400 mg) was administered as fourth-line therapy. CT imaging after one month revealed significant tumor shrinkage, including lesions outside the irradiation field. A sustained partial response was observed for four months after a single cycle of pembrolizumab. Discussion: This case demonstrates the potential efficacy of pembrolizumab in treating MSI-high thymic carcinoma, emphasizing the importance of MSI testing in such cases. Routine MSI evaluation should be considered to identify candidates for immunotherapy. Further research is needed to confirm the role of pembrolizumab in this rare malignancy and to establish its broader applicability under similar conditions.